FOSTER FAMILY AS A FORM OF CARE FOR ORPHANS AND CHILDREN DEPRIVED OF PARENTAL SWIMMING: CHALLENGES OF TODAY - Grabowska, Hanna; Galatenko, Karina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to explore the legal framework of the foster family as a form of care for orphans and children deprived of parental care during the war. Focus on improving the rules of legislation in the field of regulation of foster care in real time. Methods: literary (elaboration of literary sources, textbooks, monographs, articles from legal journals, legal norms of current legislation), documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. The multifaceted nature of the subject of research has led to the use of both general and private scientific methods. Results: the peculiarities of reforming and functioning of the system of guardianship of orphans in Ukraine under martial law are analyzed. In particular, emphasis was placed on the fact that the foster family in Ukraine must become one of the most common forms of care for orphans and children deprived of parental care. That is why the government has temporarily decided to simplify the procedure for custody of orphans and children deprived of parental care for the period of martial law in the country. Because today’s challenges are prompting many scholars and practitioners to seek to improve this form of child care. Discussion: the normative base that provides requirements for foster families and the conditions under which they can provide care for orphans and children deprived of parental care in martial law in Ukraine was analyzed. The foster family is a form of family upbringing, it also remains a form of state care for orphans and children deprived of parental care, so the state retains a number of functions: child support, wages for foster parents, methodological training and assistance them in the upbringing of orphans, control over the maintenance and upbringing of children. Also very important and relevant are the issues of creating favorable conditions for development and family upbringing of children because of them depends on the future of the country.